Status of knowledge regarding school health services among school teachers: a cross sectional study from a northern Indian state - Ranga, Aniruddh; Majra, J. P. (International Journal Of Community Medicine And Public Health, 2020)
Background: School-age children spend one-third of their time in schools. Teachers are key personnel to look after the health of school children. Teachers can provide health education to school children, assess the school environment for better health outcomes, provide health care services and help in the maintenance of school health records. Aim of the study was to assess the status of knowledge of school health services (SHS) among school teachers. Methods: Government and private schools in a Northern Indian state. A community-based cross-sectional study. It includes 50 randomly selected designated schoolteachers for SHS by the PPS methods from the schools which were functional since at least five years in the study area. A pre-tested self-administered questionnaire was used to assess the knowledge regarding SHS. Percentage, proportion and χ2 test were used as statistical methods. The p-value 0.05 was considered statistically significant. Results: 38% participants were of 41-50 years of age group, 54% were females and 48% had an experience of ≤10 years. 22% participants had training regarding SHS. 40% participants had moderately adequate knowledge (p-value=0.04). It was observed to be more among participants of rural, government, age group of 31-40 years, with experience of 21-30years, female and among trained teachers for school health. Conclusions: School teachers were lacking in knowledge regarding environment and sanitation; communicable and non-communicable diseases; and health education for school children. We also observed that training regarding SHS was a majorly missing component which could be the reason behind poor level knowledge among schoolteachers.